Gambaran Klinis dan Respon Imun Penderita Demam Berdarah Dengue di Rumah Sakit Kristen Lindi Mara Sumba Timur Selama Bulan Januari Sampai dengan Desember 2018 - Ruben Wadu Wila; Roy Nusa (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2020)
Dengue hemorrhagic fever (DHF) is an arboviral disease that is widespread worldwide. Dengue virus is transmitted to humans through the bite of an infected female Aedes mosquito. Infection of one of the viral serotypes in the majority of cases causes no symptoms or may cause clinical symptoms. Dengue virus infection causes the body to respond clinically and form antibodies. This research study is to provide clinical features and immune response in patients with Dengue hemorrhagic fever. This article uses an observational study design of secondary data of both IgM and IgG sequential examinations of 52 people with Dengue hemorrhagic fever infections at Lindi maria hospital in 2018.The results of the descriptive analysis showed that male population with Dengue hemorrhagic fever was 55.8%, and the highest rate of infection was in adolescents 34.6%. The most clinical features found were fever 91.4%; headache 24.0%; swallow pain 20.8%; vomiting 21.8%; and gastric pain18.7%. Serological examination showed 19.2% positive IgM; 36.5% IgG; and 44.2% positive both IgM and IgG. The Dengue virus infection in 52 patients in East Sumba is mostly secondary infection (80.8%) with the most infected age group is the adult group (≥ 16 years old).